Divine darkness in the human discourses of Job - N. F. Schmidt; P. J. Nel (Acta Theologica)
The Biblical Hebrew text of Job narrates and debates the suffering of an innocent person from various perspectives. The poetic dialogues and discourses between Job and his friends emphasise their experiences of “darkness” (? (??? as Divine interventions in relation to Job’s situation. The article investigates the meaning of Divine “darkness” in terms of various understandings and interpretations linked to the suffering of Job. It illustrates how the characters conceptualise the same term differently, which eventually led to a communicative disintegration in the conversations between Job, Eliphaz, Bildad, Zophar, and Elihu. Finally, in the YHWH speeches of Job 38-41, the concept of “darkness” is viewed from yet another perspective.